Marvin Ray Burns

 I've been using Maple since 1997 or so.

MaplePrimes Activity


These are Posts that have been published by Marvin Ray Burns

The MRB constant is the upper limit point of the sequence of partial sums defined by s(n)= sum((-1)^n*n^(1/n),n=1..infinity).

Each summand is a real number. However, the function f(n)= (-1)^n*n^(1/n) is a complex-valued function of a real number, n. This blog is a break in progression of the MRB constant series for the purpose of looking at the "complex" nature of this function. The function can be written in exponential form, exp(I*n*Pi)*n^(1/n).

With this first post I would like to demonstrate, in a Maple document, what happens to f [-2,0). When put together (-1,0) these graphs seem to be describing a hyperbolic spiral. I'm not sure if I'll have more to say, or not. As always, others are welcome to join in.

 

 

(1)

(2)

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 



Download f6142010.mw

 

If a function is differentiable at some point c of its domain, then it is also continuous at c. However here we extend the notion of differentiability to be valid for individual points on the real number line, specifically positive integers.

 f(n)=(-1)^n* n^(1/n)

THEOREM MRBK 8.0

f=f' / (I*Pi+(1-ln(n))/n^2)| n ∈ {1,2,3,...}

By THEOREM MRBK 4.0, When n is in the set of (positive) integers the derivative of f is exactly I*Pi*f+(1-ln(n))*f/n^2.

So f' = I*Pi*f+(1-ln(n))*f/n^2| n ∈ {1,2,3,...}

Solving for f, we have the following:

f' = I*Pi*f+(1-ln(n))*f/n^2

f' = f*(I*Pi+(1-ln(n))/n^2)

f=f' / (I*Pi+(1-ln(n))/n^2)

 

For more on this click here (W/A).

Since the MRB constant is an alternating sum of positive integers to their own roots, f(n)=(-1)^n* n^(1/n); a thorough understanding of the changes in f, as n changes, is important.
In this blog we will begin to explore the derivative of f at integer values of n, and as n-> infinity. I am not sure weather this will help us in computing more digits of the MRB constant since we already know so many,

At the end of the blog MRB constant 

Consider  S=sum((-1)^n*(n^(1/n)-a),n=1..infinity).
S=1/2*(a+2m-1), where m is the MRB constant.

Let m = MRB constant = sum((-1)^n*(n^(1/n)-1),n=1..infinity)

First 8 9 10 11 12 13 14 Page 10 of 14